Hospitality as an Organizational Culture. (March 2020) - Pizam, Abraham
This article proposes a new definition of the concept of hospitality organizational culture. It identifies its components/dimensions and suggests a conceptual framework for determining the effect of practicing a hospitality organizational culture in nonhospitality industries such as health care and retail.